Victims’ Opportunities to Review a Decision not to Prosecute made by the Crown Prosecutor - Tian, Li (2013)
In Canada, Crown prosecutors and the Attorney General are not always as fair as we expect when making charging decisions, and therefore victims could be personally aggrieved by unfair and unjust decisions not to prosecute. When this happens, victims have limited remedy to redress the unfairness and unjustness in order to uphold their interests in a criminal proceeding. Conversely, the European Union, United Kingdom, and the United State have taken steps to let victims challenge decisions not to prosecute to some extent. Drawing on experiences of the abovementioned jurisdictions, I propose a two-level process of review for decisions not to prosecute----Internal Review and Judicial Review----in Canada in order to provide victims a way to have problematic decisions reversed. This proposal can provide a direction or framework for future reform in this area in Canada